(untitled) (Medical Forum Monthly, 2024)
Background: In spite of the belief that cancer mortality can be reduced if lesions are detected, diagnosed and treated at an early stage. There is a concurrent increase in advanced head and neck cancer patients, because of delayed in medical consultations. Objectives: The objective of this study is to determine an association of staging and diagnostic delay in oral cancer patients. Study Design: Descriptive study. Place and Duration of Study: This study was conducted at the Dow Diagnostic & Research Laboratory (DDRL) of the Ojha Campus, Dow University of Health Sciences from Jan 2009 to April 2011. Materials and Methods: The information is collected from the record files of DDRL of OJHA campus DUHS. Two hundred and seventy nine patients with an oral cancer are included in the study. Results: With descriptive statistics, OSCC is mostly found at 4th, 5th and 6th decades of life, with diagnostic delay of ≥ 6 months. OSCC is mostly seen in males than in females whereas; Well differentiated squamous cell carcinoma is a common finding in both males and females, with the largest lesion being size 12 cm in size. Buccal mucosa is a commonly affected site in both genders. OSCC is mostly seen in males than in females. Conclusion: Our findings highlight the importance of early detection and systemized collection of patients verbal statements regarding their initial symptoms of oral cancer.